Steuerungswirkungen der Hochschulfinanzierung in Deutschland - Fischer, Georg-Benedikt (KIT Scientific Publishing, 2014)
The work analyses different forms and effects of higher education funding. In the beginning, the determinants of higher education spending by the German federal states are studied. Then the thesis focuses on the recent introduction of tuition fees at public universities in Germany to identify the effects of tuition fees on the enrollment decision of first year students. In addition, the impact of tuition fees is compared with the effect of administrative fees.